PENGGUNAAN BAHASA ALAY TERHADAP BAHASA INDONESIA YANG BAIK DAN BENAR - dra.gusnayetti gusnayetti (Jurnal Administrasi Publik dan Pemerintahan, 2023)
Alay language is a language feature that sounds strange and the meaning and writing of alay language is strange and beyond reason and common sense from the speech used by our nation, the Indonesian people. Before discussing further about the problems that have been formulated, it is better if we know a little about the beginning of the Alay language. There is no certainty when alay language began to mushroom among teenagers. However, basically, without us realizing it, signs of alay language have existed for a long time and we must have used alay language. At first glance, it can be said that alay language is the same as broken language or slang. This research uses a qualitative approach. Research that uses research results in the form of alay language in adolescents and describes it in written form. This technique is carried out after the data has been collected with the listening method so that it can show usage through observation, conversation, documentation. This data technique uses the listen method, this method is done by reading the speech of teenagers to find out the language used. Reading technique aims to get data in the form of words or sentences that teenagers write.